Asymmetric syntheses of methyl N-Boc-2-deoxy-2-amino-L-erythroside, methyl N-Boc-2-deoxy-2-amino-D-threoside and methyl N-Boc-2,3-dideoxy-3-amino-L-arabinopyranoside - Brambilla, M; Davies, S; Fletcher, A; Hao, L; Lv, L; Roberts, P; Thomson, J (2014)
The asymmetric syntheses of methyl N-Boc-2-deoxy-2-amino-l-erythroside and methyl N-Boc-2-deoxy-2-amino-d-threoside have been achieved from sorbic acid, in six and eight steps, and in 35 and 13% overall yield, respectively. Diastereoselective aminohydroxylation of tert-butyl sorbate gives access to two diastereoisomeric α-hydroxy-β-amino-γ,δ-unsaturated esters. Reduction of the ester functionality and ozonolysis of the double bond gives the corresponding aldehyde, which exists exclusively in the ring-closed (furanose) form. An alternative synthesis of methyl N-Boc-2-deoxy-2-amino-l-erythroside was also developed, reliant on aminohydroxylation of an α,β-unsaturated ester bearing an acetal functionality at the γ-position, and this synthesis proceeded in five steps and 54% overall yield from acrolein diethyl acetal. This approach was extended to permit the synthesis of methyl N-Boc-2,3-dideoxy-3-amino-l-arabinopyranoside in six steps and 58% overall yield from ethyl 3,3-diethoxypropanote. © 2014 Elsevier Ltd. All rights reserved.